Prediction of flow induced vibration of a flat plate located after a bluff wall mounted obstacle. Issue 190 (July 2019) - Torregrosa, A.; Gil, A.; Quintero, P.; Ammirati, A.; Denayer, H.; Desmet, W.
Abstract: Accurate prediction of Flow Induced Vibration phenomena is currently a field of major interest due to the use of lightweight materials in the automotive and aerospace industry. This article studies the turbulent flow around a wall-mounted obstacle, and the induced deformations produced by the pressure fluctuations on a plate located downstream the obstacle. The methodology used is a combination of experimental tests and numerical simulations. On one side, experiments were carried out in a wind tunnel test facility equipped with Particle Image Velocimetry to characterize the fluid velocity field, and laser vibro-meter to measure the vibrations of the plate. On the other side, Fluid-Structure Interaction (FSI-one-way) has been calculated by considering different turbulence modeling approximations (RANS and LES). Finally, numerical results have been analyzed and validated against the experiments in terms of main flow structures and the vibroacoustic response of the plate.